Optimizing long passing: a study on the relationship between waist flexibility in soccer players - Mardepi Saputra; Aldo Naza Putra; Sepriadi Sepriadi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction. Starting from the shortcomings found from previous studies regarding the relationship between physical factors and technical abilities in football, so the background for us to make this research.